إدارة الانفعالات وعلاقتها بموقع الضبط لدى طلبة الجامعة - منصور حسين المحسن, رضاب (Journal of College of Education, 2020)
In the light of the identified research objectives as follows :           1 –The level of Emotions Management of university students 2- The difference in the middle degrees of Emotions Management                     according to the variables (Gender , specialization , class).                    3- The level of Locus control of university students .   4- The difference in the middle degrees of Locus control                     according to the variables ( Gender , specialization , class).                         5- The relationship between the Emotions Management and Locus control of university students .and on the search results have been indicated to the following:1-The sign of the difference in the answers to students on scale at the level of Emotions Management (0.05) for the sample average  2-The sign of the difference in the degrees of Locus control to the variable of sex differences that are statistically significant at the level of (0.05) the sign of difference refer to proposition average .3-The sign of the difference on scale Emotions Management   at the level of  (0.05) for the sample average .4- The sign of the difference in the degrees of Locus control  to the variable of sex differences that are statistically significant at the level of (0.05) the sign of difference refer to proposition average .                     Recommendations :  1- Enrich the curriculum of Emotions Management at the college studyOne of the main proposals:1- Doing a survy aims at discovering the other changeable that are not dealt with in present study(the salutation problems--) to the university students .